Cyclic ADP-Ribose and Heat Regulate Oxytocin Release via CD38 and TRPM2 in the Hypothalamus during Social or Psychological Stress in Mice - Zhong, Jing; Amina, Sarwat; Liang, Mingkun; Akther, Shirin; Yuhi, Teruko; Nishimura, Tomoko; Tsuji, Chiharu; Tsuji, Takahiro; Liu, Hong-Xiang; Hashii, Minako; Furuhara, Kazumi; Yokoyama, Shigeru; et al. (Frontiers in Neuroscience, 2016)
Hypothalamic oxytocin (OT) is released into the brain by cyclic ADP-ribose (cADPR) with or without depolarizing stimulation. Previously, we showed that the intracellular free calcium concentration ([Ca2+]i) that seems to trigger OT release can be elevated by -NAD+, cADPR, and ADP in mouse oxytocinergic neurons. As these -NAD+ metabolites activate warm-sensitive TRPM2 cation channels, when the incubation temperature is increased, the [Ca2+]i in hypothalamic neurons is elevated. However, it has not been determined whether OT release is facilitated by heat in vitro or hyperthermia in vivo in combination with cADPR. Furthermore, it has not been examined whether CD38 and TRPM2 exert their functions on OT release during stress or stress-induced hyperthermia in relation to the anxiolytic roles and social behaviors of OT under stress conditions. Here, we report that OT release from the isolated hypothalami of male mice in culture was enhanced by extracellular application of cADPR or increasing the incubation temperature from 35°C to 38.5°C, and simultaneous stimulation showed a greater effect. This release was inhibited by a cADPR-dependent ryanodine receptor inhibitor and a nonspecific TRPM2 inhibitor. The facilitated release by heat and cADPR was suppressed in the hypothalamus isolated from CD38 knockout mice and CD38- or TRPM2-knockdown mice. In the course of these experiments, we noted that OT release differed markedly between individual mice under stress with group housing. That is, when male mice received cage-switch stress and eliminated due to their social subclass, significantly higher levels of OT release were found in subordinates compared with ordinates. In mice exposed to anxiety stress in an open field, the cerebrospinal fluid (CSF) OT level increased transiently at 5 minutes after exposure, and the rectal temperature also increased from 36.6°C to 37.8°C. OT levels in the CSF of mice with lipopolysaccharide-induced fever (+0.8°C) were higher than those of control mice. The TRPM2 mRNA levels and immunoreactivities increased in the subordinate group with cage-switch stress. These results showed that cADPR/CD38 and heat/TRPM2 are co-regulators of OT secretion and suggested that CD38 and TRPM2 are potential therapeutic targets for OT release in psychiatric diseases caused by social stress.